Patient Claim Financing at RSUP Dr. Kariadi Semarang During the Covid-19 Pandemic (Unnes Journal of Public Health, 2022)
Findings on the health status and condition of patients who came to Dr. Kariadi were classified into two categories comorbid and co-incident. For patient claims to be funded, an assembling process and case-mix coding are carried out for the submission process based on the results of checking the status and health conditions of comorbid and co-incident patients. This study explores the procedure for the process of financing the patient's claim at Dr. RSUP. Kariadi Semarang during the covid-19 pandemic. The research was conducted in a phenomenological descriptive qualitative manner with the data sources coming from primary informants. Sampling technique with the selection according to the criteria then conducted an interview. Flow analysis model and interactive analysis model were used to analyze the data. For Covid-19 patients with comorbidities, previously a claim was made for Covid-19 cases, and if the Covid-19 case was completed but the comorbidities persisted, the guarantor switched from the Ministry of Health to BPJS Health. The procedure for the process of financing a patient's claim at Dr. RSUP. Kariadi Semarang during the COVID-19 pandemic there were two guarantors from the Ministry of Health and BPJS Health.